Describing the Relationships between Tourist Satisfaction and Destination Loyalty in a Segmented and Digitalized Market - Bart Neuts; Jo\~ao Rom\~ao; Eveline van Leeuwen; Peter Nijkamp (Tinbergen Institute, 2013)
As a result of advances in ICT-services, transportation, and local development, among others, an increasing number of destinations is competing to attract both national and international visitors. Globalisation requires destinations to increase their competitiveness or risk losing out on tourist revenues. While the research into destination competitiveness and tourist loyalty is well founded, recent progress in e-services has opened new opportunities for informing and attracting visitors. This paper examines the potential effects of e-services in an inclusive model of destination loyalty towards the city of Leipzig (Germany). The results of the path analysis indicate possibilities for e-services to increase both satisfaction and loyalty, especially with regard to a number of tourist subgroups.
Keywords: L83; L86; 330; Loyalty; E-services; ICT; Satisfaction; Destination Management